Pendeteksian Osilasi Mikro Dengan Interferometer Michelson Berbantuan Komputer = Detection of Micro Oscillation with Michelson Interferometer Based Personal Computer - Perpustakaan UGM, i-lib ([Yogyakarta] : Lembaga Penelitian dan Pangabdian kepada Masyarakat, Universitas Gadjah Mada, 1999)
ABSTRACT One of the mirrors of Michelson interferometer was glued to a pivot of a loud-speaker connected to an Audio Frequency Generator (AFG) or vibrating objects, and the pattern of interference was produced on its screen with different intensity as time function. The variation of intensity affected the phase modulation of the laser. Using photodiode equipped amplifier circuit, the variation of the intensity was converted into voltage variation. The photodiode was placed on the center of the interference pattern. The voltage variation observed, recorded, and analyzed by Turbo Pascal programming. The ADC card was used to connect the computer to the photodiode and its ADC card had been made in 12 bit resolution. The measurement using optical method could detect the vibration which had very small amplitude (in order to wavelength of ray used) and did not give any load to vibrating object. The measurement of object frequency ranged from several Hertz to hundred Hertz and object amplitudes of vibration up to several times of laser beam wavelength adopted. The result of the measurement was not different from theoretical prediction.